Bio-Anthropological Studies on Human Skeletons from the 6th Century Tomb of Ancient Silla Kingdom in South Korea - Lee, Won-Joon; Woo, Eun Jin; Oh, Chang Seok; Yoo, Jeong A.; Kim, Yi-Suk; Hong, Jong Ha; Yoon, A. Young; Wilkinson, Caroline M.; Ju, Jin Og; Choi, Soon Jo; Lee, Soong Doek; Shin, Dong Hoon (PLOS ONE, 2016)
In November and December 2013, unidentified human skeletal remains buried in a mokgwakmyo (a traditional wooden coffin) were unearthed while conducting an archaeological investigation near Gyeongju, which was the capital of the Silla Kingdom (57 BCE– 660 CE) of ancient Korea. The human skeletal remains were preserved in relatively intact condition. In an attempt to obtain biological information on the skeleton, physical anthropological, mitochondrial DNA, stable isotope and craniofacial analyses were carried out. The results indicated that the individual was a female from the Silla period, of 155 ± 5 cm height, who died in her late thirties. The maternal lineage belonged to the haplogroup F1b1a, typical for East Asia, and the diet had been more C3- (wheat, rice and potatoes) than C4-based (maize, millet and other tropical grains). Finally, the face of the individual was reconstructed utilizing the skull (restored from osseous fragments) and three-dimensional computerized modeling system. This study, applying multi-dimensional approaches within an overall bio-anthropological analysis, was the first attempt to collect holistic biological information on human skeletal remains dating to the Silla Kingdom period of ancient Korea.